Potential alternatives of animal proteins for sustainability in the food sector - Kumar, Pavan; Mehta, Nitin; Abubakar, Ahmed Abubakar; Verma, Akhilesh Kumar; Kaka, Ubedullah; Sharma, Neelesh; Sazili, Awis Qurni; Pateiro, Mirian; Kumar, Manoj; Lorenzo, José M. (Taylor and Francis Group, 2022)
With the ever-increasing global population, it is impossible to meet the demand for animal protein by relying only on conventional methods due to the depleting natural resources. It is very challenging to ensure a sustainable supply of animal proteins from a single source or form and requires a holistic approach by using all suitable options. The present review critically reviewed various technological, sustainability, nutritional value, regulatory framework, food safety challenge, and prospect aspects of plant-based meat analogs, in vitro meat, edible insect, and single-cell proteins as suitable candidates for future food security and supply of animal protein in a sustainable way. For in vitro meat, the technological challenge in the supply of raw inputs, large-size bioreactors, and scale-up remains a major issue. Although having a lower environmental impact, the acceptance of edible insects to more comprehensive sections and associated food safety risks remains a major concern. There is a need for uniform and proper regulations of these alternatives/novel foods across the globe, covering various aspects throughout the food supply chain. Plant-based meat analogs, in vitro meat, insects, and single-cell proteins along with conventional meat can meet the demand for high-quality protein in the near future.